An uneasy relationship : Norfolk Island and the commonwealth of Australia - O'Collins, Maev (Pandanus Books, 2002)
The struggle of one Norfolk Islander, Charles Chase Robinson Nobbs, against Australian administrative authority, as Norfolk islanders try to maintain their socio-politic identity in the South Pacific.